2014
DOI: 10.1161/strokeaha.113.003368
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Is a Critical Time to Influence 10-Year Use of Secondary Prevention Therapies for Stroke

Abstract: Background and Purpose— When optimally managed, patients with stroke are less likely to have further vascular events. We aimed to identify factors associated with optimal use of secondary prevention therapies in long-term survivors of stroke. Methods— We carefully documented discharge medications at baseline and self-reported use of medications at annual follow-up in the Northeast Melbourne Stroke Incidence Study (NEMESIS). We defined optimal medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…Overall, the patients managed on ASUs were less often discharged to institutional residential aged care (6% ASU versus 11% other wards, P<0.001) and more often accessed inpatient rehabilitation (37% ASU versus 22% other wards, P<0.001). (16) 2111 (15) 404 (16) 223 (27) IRSAD 2 3614 (21) 2875 (21) 495 (19) 244 (29) IRSAD 3 2173 (13) 1778 (13) 309 (12) 86 (10) IRSAD 4 3707 (21) 3026 (22) 523 (20) 158 ( (11) 1171 (9) 694 (27) 82 (11) Home 6603 (39) 5664 (41) 546 (22) 393 (51) Rehabilitation 5181 (30) 4389 (32) 705 (28) 87 (11) Institutional care 1014 (6) 777 (6) 176 (7) 61 (8) Hospital readmission within 90-180 d* 1577 (20) 1354 (20) 154 (19) 69 (23) Figure). Receiving care bundle (a) (ASU care) was strongly associated with greater 180-day survival (hazard ratio, 0.49; 95% CI, 0.43-0.56; Table 3) and HRQoL (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the patients managed on ASUs were less often discharged to institutional residential aged care (6% ASU versus 11% other wards, P<0.001) and more often accessed inpatient rehabilitation (37% ASU versus 22% other wards, P<0.001). (16) 2111 (15) 404 (16) 223 (27) IRSAD 2 3614 (21) 2875 (21) 495 (19) 244 (29) IRSAD 3 2173 (13) 1778 (13) 309 (12) 86 (10) IRSAD 4 3707 (21) 3026 (22) 523 (20) 158 ( (11) 1171 (9) 694 (27) 82 (11) Home 6603 (39) 5664 (41) 546 (22) 393 (51) Rehabilitation 5181 (30) 4389 (32) 705 (28) 87 (11) Institutional care 1014 (6) 777 (6) 176 (7) 61 (8) Hospital readmission within 90-180 d* 1577 (20) 1354 (20) 154 (19) 69 (23) Figure). Receiving care bundle (a) (ASU care) was strongly associated with greater 180-day survival (hazard ratio, 0.49; 95% CI, 0.43-0.56; Table 3) and HRQoL (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…15,16,21,22 The cohort presented here had, by comparison, unusually high levels of overall statin adherence; it is possible that the right-shifted distribution of PDC shown in Figure 1A may be because of the integrated nature of the healthcare delivery system from which the data are derived. Given that hospital discharge has been shown to be a critical moment to impact long-term adherence to the secondary stroke prevention strategies, 23 it is possible that our previously reported EMR intervention to increase statin prescription during stroke hospitalization 13 may have also contributed to long-term statin adherence in this cohort.…”
Section: Discussionmentioning
confidence: 95%
“…At 2 years, they observed that antiplatelet agents, warfarin, antihypertensive agents and statins had declined to 63.7, 45, 74.2 and 56.1% respectively. A more recent study looking at the use of secondary preventive treatment 10 years after stroke [11] found that the proportion of ­patients treated by antithrombotic drugs declined globally from 92 to 78% without further details. In contrast, compared to discharge, antihypertensive agent use increased from 58 to 74% and statin use increased from 21 to 48%.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of therapies including antiplatelet drugs, antihypertensive agents and statins have clearly shown their efficacy in reducing the risk of vascular events in stroke patients [4]. Despite this evidence, there is a gap between guidelines and observed medication use: after a stroke, less than 50% of patients with known atrial fibrillation are on anticoagulant treatment, 70–85% of patients eligible for antiplatelet agents receive this treatment, 45–75% of patients are on antihypertensive agents and 20–50% of patients are on statins [5-11]. …”
Section: Introductionmentioning
confidence: 99%